Kinerja Kelompok Tani pada Gapoktan Tunjung Mekar Dalam Pengembangan Usaha Agribisnis Perdesaan (PUAP) Pada Desa Macang Kecamatan Bebandem Kabupaten Karangasem - PRADNYA ARUNA WIJAYA; DWI PUTRA DARMAWAN; A.A.A WULANDIRA SAWITRI DJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
The Performance of Tunjung Mekar Farmer Group in Rural Agribusiness Development in Macang Village, Bebandem District, Karangasem Regency. Rural Agribusiness Development (PUAP) is a medium-term government program that focuses on rural agricultural development. One of the farmer group associations that implement this program is Gapoktan Tunjung Mekar in Macang Village, Bebandem District, Karangasem Regency. This study involves 16 participants who are the heads and secretaries of each farmer group. Using a qualitative descriptive method, this study shows that the performance of Gapoktan Tunjung Mekar in developing PUAP can be categorized as a beginner with a score of <250. There is only one subak, namely Subak Macang which is included in the intermediate category with a score of 433. PUAP has an impact in the form of additional capital for each farmer group by an average of 48.25%, so that the final capital obtained is IDR 148,250,000 from the initial capital. IDR 100,000,000.